EFL Writing Courses in the Age of Generative AI: University EFL Students’ Perceptions - Fallatah, Rajaa (International Journal of Language and Literary Studies, 2026)
At this point, the positive effects and challenges of using AI-based chatbots and tools in EFL classrooms are increasingly prominent in the scholarly literature. Nevertheless, Saudi EFL students’ perceptions of the impact, benefits, and challenges of using AI chatbots to enhance their writing skills remain underexplored. To address this gap, the present study investigates the perceptions of 100 Saudi EFL students regarding generative AI chatbots, particularly ChatGPT, in writing instruction through an online survey. The survey data were analyzed in SPSS using multiple analytical methods, including descriptive statistics, correlation, and regression. The results show that the students have very high perceptions of the benefits of using ChatGPT to enhance their writing. In addition, results indicate that students’ perceptions of ChatGPT’s impact and limitations, and their awareness of factors to consider when using it, were rated highly. Furthermore, the results demonstrate that students’ perceptions are significantly correlated with self-reported proficiency, suggesting that higher proficiency is associated with more positive attitudes towards AI tools for enhancing EFL students’ writing skills. Practical implications for EFL students and educators are discussed, emphasizing the value of incorporating AI to facilitate the development of writing skills. Directions for future research are also highlighted at the conclusion of this study.